2022
DOI: 10.3390/membranes12030284
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Circuit Design, Structural, Relaxation and Potential Stability of Polymer Blend Electrolyte Membranes Based on PVA:MC Impregnated with NH4I Salt

Abstract: This work presents the fabrication of polymer electrolyte membranes (PEMs) that are made of polyvinyl alcohol-methylcellulose (PVA-MC) doped with various amounts of ammonium iodide (NH4I). The structural and electrical properties of the polymer blend electrolyte were performed via the acquisition of Fourier Transform Infrared (FTIR) and electrical impedance spectroscopy (EIS), respectively. The interaction among the components of the electrolyte was confirmed via the FTIR approach. Electrical impedance spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 90 publications
1
13
0
Order By: Relevance
“…The decrease in electrical resistance along with the increase in lithium salt addition to the solid polymer electrolyte membranes was indicated in several previous studies, such as PVA: MC: NH 4 I electrolyte-based membranes, 58 where the ammonium iodide decreased the electrical resistance of the membrane. Another study reported that the increase in the addition of Mg(NO 3 ) 2 decreases the bulk resistance (R b ) in the pectin-based/Mg (NO 3 ) electrolyte membrane.…”
Section: Ionic Conductivity Analysissupporting
confidence: 55%
“…The decrease in electrical resistance along with the increase in lithium salt addition to the solid polymer electrolyte membranes was indicated in several previous studies, such as PVA: MC: NH 4 I electrolyte-based membranes, 58 where the ammonium iodide decreased the electrical resistance of the membrane. Another study reported that the increase in the addition of Mg(NO 3 ) 2 decreases the bulk resistance (R b ) in the pectin-based/Mg (NO 3 ) electrolyte membrane.…”
Section: Ionic Conductivity Analysissupporting
confidence: 55%
“…Electrochemical impedance spectroscopy (EIS) has been used extensively in the investigation of electrochemical behaviour and ion transport in a range of ionic materials, including electrodes and SPEs. Using this method, impedance spectra for the SPE films were generated and analyzed [ 44 , 45 ]. All impedance spectra observed in this study showed a prominent spike at low frequency, due to double layer capacitance which existed at the interface of the electrode and the electrolyte sample.…”
Section: Resultsmentioning
confidence: 99%
“…A closer look at the impedance spectra showed a tiny semicircle at the high frequency region of most of the samples. This was attributed to the bulk resistance (R b ) of the electrolyte samples [ 44 ]. Here, the value of R b was obtained by measuring the point at which the semicircle touched the real impedance axis (Z r ), just before the spike.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in peak location imply principally the change in the state of the electron dispersion or hybridization inside the chemical bond. Typically, a reduction in peak intensity indicates a decrease in the number of functional groups linked with the molecular bond (per unit volume) [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%